PEMOCS: theory derivation of a concept for PErsonalized MOtor-Cognitive exergame training in chronic Stroke—a methodological paper with an application example - Huber, Simone K.; Manser, Patrick; de Bruin, Eling D. (Frontiers in Sports and Active Living, 2024)
Coping with residual cognitive and gait impairments is a prominent unmet need in community-dwelling chronic stroke survivors. Motor-cognitive exergames may be promising to address this unmet need. However, many studies have so far implemented motor-cognitive exergame interventions in an unstructured manner and suitable application protocols remain yet unclear. We, therefore, aimed to summarize existing literature on this topic, and developed a training concept for motor-cognitive exergame interventions in chronic stroke.The development of the training concept for personalized motor-cognitive exergame training for stroke (PEMOCS) followed Theory Derivation procedures. This comprised A1) a thorough (narrative) literature search on long-term stroke rehabilitation; A2) a wider literature search beyond the topic of interest to identify analogies, and to induce creativity; B) the identification of parent theories; C) the adoption of suitable content or structure of the main parent theory; and D) the induction of modifications to adapt it to the new field of interest. We also considered several aspects of the 'Framework for Developing and Evaluating Complex Interventions' by the Medical Research Council. Specifically, a feasibility study was conducted, and refining actions based on the findings were performed.A training concept for improving cognitive functions and gait in community-dwelling chronic stroke survivors should consider the principles for neuroplasticity, (motor) skill learning, and training.We suggest using a step-based exergame training for at least 12 weeks, 2-3 times a week for approximately 45 minutes. Gentile's Taxonomy for Motor Learning was identified as suitable fundament for the personalized progression and variability rules, and extended by a third cognitive dimension. Concepts and models from related fields inspired further additions and modifications to the concept.We propose the PEMOCS concept for improving cognitive functioning and gait in community-dwelling chronic stroke survivors, which serves as a guide for structuring and implementing motor-cognitive exergame interventions. Future research should focus on developing objective performance parameters that enable personalized progression independent of the chosen exergame type.